2010
DOI: 10.1002/adfm.201001446
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Monitoring of the Solid-State Microstructure Evolution of Polymer:Fullerene Blend Films Using Field-Effect Transistors

Abstract: Organic fi eld-effect transistors (OFETs) are used to investigate the evolution of the solid-state microstructure of blends of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C 61 -butyric acid methyl ester (PC 61 BM) upon annealing. Changes in the measured fi eld-effect mobility of holes and electrons are shown to reveal relevant information about the phase-segregation in this system, which are in agreement with a eutectic phase behavior. Using dualgate OFETs and in-situ measurements, it is demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 57 publications
3
55
1
Order By: Relevance
“…[ 31 ] We hence consider our observation of a reduction in electron mobility as a useful indicator that phase-segregation is taking place, rather than suggest that phase-segregation leads to a reduction of electron mobility in OPV structures. [ 31 ] By studying the conditions under which the electron mobility falls in such OFET devices, it is hoped that information relevant to OPV fabrication and optimization can be elucidated. Upon annealing at 220 ° C the hole mobility starts to fall and the electron mobility begins to recover.…”
Section: P3ht:pc 71 Bm Blend Based Transistorsmentioning
confidence: 98%
See 3 more Smart Citations
“…[ 31 ] We hence consider our observation of a reduction in electron mobility as a useful indicator that phase-segregation is taking place, rather than suggest that phase-segregation leads to a reduction of electron mobility in OPV structures. [ 31 ] By studying the conditions under which the electron mobility falls in such OFET devices, it is hoped that information relevant to OPV fabrication and optimization can be elucidated. Upon annealing at 220 ° C the hole mobility starts to fall and the electron mobility begins to recover.…”
Section: P3ht:pc 71 Bm Blend Based Transistorsmentioning
confidence: 98%
“…[ 31 ] The p-and n-channel transfer characteristics of an un-annealed P3HT:PC 71 BM (1:1 wt%) BCBG ambipolar OFET are shown in Figure 1 (b). With gold source and drain electrodes, such polymer:fullerene OFETs are known to be capable of injecting and transporting holes in the polymer network and electrons in the fullerene network, but not nice-versa.…”
Section: P3ht:pc 71 Bm Blend Based Transistorsmentioning
confidence: 99%
See 2 more Smart Citations
“…13). 124 They used FET measurements on P3HT/PCBM blends annealed at different temperatures and reported that the hole and electron mobilities remain constant till the annealing temperature of 140 C. However, upon annealing above this temperature, the hole mobility increases while the electron mobility drastically decreases. The observed effect was attributed to the increased crystallization in the P3HT domains and the increased clustering of PCBM.…”
Section: Field-effect Transistorsmentioning
confidence: 99%